Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan Dan Profitabilitas Terhadap Manajemn Laba (Study Empiris Perusahaan Sektor Pertambangan Pada Bei Tahun 2013 – 2018) - Faisol, Imam Agus (Unversitas Islam Madura, 2020)
This study aims to examine the effect of tax planning, deferred tax expense and profitability on the earnings management. The population of this research is all mining companies listed on the Indonesia Stock Exchange (IDX) in 2013 to 2018. Sampling using purposive sampling method, the sample is selected using certain considerations that are tailored to the purpose of research or study problems developed so that the sample in this study amounted to 7 companies in the third period of the study to 42 companies. The results of this study indicate that tax planning has no effect on earnings management because earning management by managers tends to occur because self-interest management is not because of principal interest, deferred tax expenses affect earning management and profitability does not affect earning management because profitability is the main concern of stakeholders interests so that management has few gaps to do earning mnagemnet